Trends and patterns in the recent accumulation and oxygen isotopes in coastal Dronning Maud Land, Antarctica: interpretations from shallow ice cores - Isaksson, Elisabeth; Melvold, Kjetil (Annals of Glaciology, 2002)
To investigate recent variability in accumulation and δ18O, we synthesize data from five snow cores, covering the period 1932–96, from the sector 16˚38’ W–4˚48’ E in coastal Dronning Maud Land (DML), Antarctica. the δ18O records from the different sites are remarkably similar and suggest a common stable moisture source for this coastal section of DML. While the accumulation pattern is local, and specific features restricted to the individual sites, the overall accumulation pattern is related to the temperature variability as indicated by coastal instrumental records. Accumulation and δ18O correlate between 1955 and 1985 but deviate thereafter, with the proxy-temperature record showing a positive trend while accumulation decreased. This occurs at the same time as an increase in sea-ice extent in the area, which may have resulted in circulation changes and more northerly storm paths. Both stacked accumulation and δ18O records show that large-scale atmospheric signals, as well as some pronounced individual events, are recorded in DML coastal ice cores.
Keywords: Dronning Maud Land; glasiologi; iskjerner

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern

Construction and operation of Troll Runway: initial environmental evaluation - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute, 2002)
Keywords: Dronning Maud Land; logistikk; luftfart

Measuring ice shelf draft and seabed topography below Fimbulisen - Nøst, Ole Anders; Goodwin, Harvey; Rønstad, Tore; Thorsen, Stein Hugo (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; glasiologi; havbunnen; isbreer; isshelf; kontinentalsokkel; topografi

Sea ice concentration off Dronning Maud Land, Antarctica - Pavlova, Olga; Winther, Jan-Gunnar (Norsk Polarinstitutt, 2002)
This project was undertaken by the Norwegian Polar Institute for the Norwegian Petroleum Directorate (Oljedirektoratet) as support for planning of marine geophysical surveys offshore from Dronning Maud Land (DML), Antarctica. The project was carried out by scientists Olga Pavlova and Jan-Gunnar Winther at the Norwegian Polar Institute under the direction of Morten Sand at the Norwegian Petroleum Directorate. The main objectives of the project were to: a) calculate 10-day average historical (i.e., 1978-1996) sea ice concentrations off DML for the months of December through April b) identify the minimum and maximum sea ice extent occurring in the period 1978-1996 c) present the above information graphically. Daily microwave satellite data covering the period 1978-1996 with 25 x 25 km spatial resolution were used as basis for this study (see text below for description of data set).
Keywords: Dronning Maud Land; havis; kartlegging; marin geofysikk; meteorologi; sjøis

Studies of population dynamics and life history strategies of Antarctic petrels at Svarthamarehn - Tveraa, Torkild; Birkeland, Ingve; Henden, John-André; Varpe, Øystein (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

Norwegian Antarctic Research Expedition (NARE) 2000/2001 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 2002)
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; geodesi; glasiologi; logistikk; marin biologi; miljøvern; naturressurser

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi